The 2015 NU Muktamar : further conservation turn in Indonesian Islam - Alexander, R. Arifianto (2015)
One key issue contested during the recent Nahdlatul Ulama congress is the debate over Islam Nusantara. However, the idea was drowned bby a tussle for leadership.